Inflammatory Markers as Predictors of Multi-Organ Involvement in Chronic Diseases: A Prospective Observational Study. - Kumar, Rajeev; Ranjan, Dr. Rajeev; Astik, Shachindra Kumar (Student’s Journal of Health Research Africa, 2026)
Background: Chronic diseases are often associated with persistent systemic inflammation, which may contribute to progressive multi-organ dysfunction. Inflammatory biomarkers such as C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), interleukin-6 (IL-6), and neutrophil-to-lymphocyte ratio (NLR) have been proposed as potential indicators of disease severity and organ involvement. Objective: To evaluate the predictive value of inflammatory markers (CRP, ESR, IL-6, and NLR) for multi-organ involvement among patients with chronic diseases. Methods: A prospective observational study was conducted over a 12-month period at Nalanda Medical College and Hospital, Patna, India. A total of 100 adult patients diagnosed with chronic diseases were included. Baseline inflammatory markers, including CRP, ESR, IL-6, and NLR, were measured. Organ involvement (cardiac, renal, hepatic, and pulmonary) was assessed through clinical evaluation, laboratory investigations, and imaging studies. Statistical analysis included descriptive statistics, independent t-tests, Pearson correlation analysis, and logistic regression to determine associations between inflammatory markers and organ involvement. Results: Multi-organ involvement was observed in 46% of patients. Mean levels of CRP, IL-6, and NLR were significantly higher among patients with involvement of two or more organs (p < 0.001). IL-6 demonstrated the strongest correlation with the number of organs involved (r = 0.62), followed by CRP (r = 0.58). Conclusion: Elevated inflammatory markers, particularly IL-6 and CRP, are strong predictors of multi-organ involvement in patients with chronic diseases and may serve as useful tools for early risk stratification.